PENGARUH STRATEGI PEMASARAN DIGITAL MELALUI LIVE STREAMING DAN AFFILIATE MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION MUSLIM DI TIKTOK JAWA TIMUR - Siti Habibatur Rahma; Siti Shoimatul Azizah; Nuril Qomariyah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2025)
Businesses must use digital marketing as a strategic tool to address customers' increasingly digital behavior when doing transactions and searching for information. This study's main goal is to analyze live streaming and affiliate marketing strategies that influence consumers' decisions to purchase Muslim fashion items on TikTok, East Java. The purpose of this is to increase knowledge about how these strategies affect the decision to buy on social media platforms. In addition, it is anticipated that this research will help businesses develop more competitive and appropriate marketing strategies for this competitive digital platform. The research methodology in this study is quantitative and uses purposive sample collection from respondents who use Tiktok in Jawa Timur. Data is collected using a questionnaire with a Likert scale, and SPSS software is used to analyze Berganda regressions. The results of the uji indicate that live streaming has a positive significant impact on sales, with a thitung value of 5,488 that is higher than the ttabel value of 1,985; affiliate marketing has a negative significant impact on sales, with a thitung value of 5,031 that is lower than the ttabel value of 1,985; and both of them have a simultaneous (joint) impact on sales with an Fhitung value of 19,574.